1999
DOI: 10.4269/ajtmh.1999.61.505
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic impact of hepatitis E in Nepal.

Abstract: Abstract. Hepatitis E disease is responsible for substantial morbidity in Nepal. A socioeconomic analysis was performed to describe the costs and the effects of hepatitis E disease (HE) on health status in a Nepalese population living in the Kathmandu Valley. A modified health status index was used to quantify healthy days lost associated with HE. One hundred thirty-four individuals recently recovered from HE were interviewed in June 1998. The median age was 22 years and 60% were female. Study participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The average total direct costs for HIV treatment in our study were higher than reported for tuberculosis, water borne diseases and malaria treatment in Nepal [31–33]. However, we cannot compare other studies in Nepal with costs of kala-azar (visceral leishmaniosis or VL) [8, 34], and hepatitis E treatment [35] because of methodological differences in calculation of the costs.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The average total direct costs for HIV treatment in our study were higher than reported for tuberculosis, water borne diseases and malaria treatment in Nepal [31–33]. However, we cannot compare other studies in Nepal with costs of kala-azar (visceral leishmaniosis or VL) [8, 34], and hepatitis E treatment [35] because of methodological differences in calculation of the costs.…”
Section: Discussionmentioning
confidence: 60%
“…The findings of the studies on kala-azar (VL) [34, 39], hepatitis E [35] and malaria [33] could not be compared because of methodological differences in calculating days lost, since these studies calculated costs on a per episode basis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little evidence of common long-term sequelae of HEV genotype 1 infections, the fatality associated with hepatitis E in pregnancy and the economic burden of this disease require that resources be committed to improving our understanding of a virus that has been ''emerging'' for nearly 3 decades (1,41,42). Our data begin to shed light on the population burden of HEV in rural Bangladesh; considering its~150 million population,~70% of whom are rural inhabitants, it is important to recognize the true potential burden of hepatitis E, especially as the means to control this infection are within our grasp (43).…”
Section: Discussionmentioning
confidence: 99%
“…The illness cost each individual an average of $37, which amounted to 19.4% of his or her yearly income. 22 In China, the average illness duration was almost 23 days and cost each patient an average of 10,655 RMB ($1673 USD). 23 Researchers estimated that the disease burden of a 2007 to 2009 epidemic of hepatitis E in Kitgum, Uganda amounted to 7,066 DALYs (disability adjusted life years).…”
Section: Burden Of Diseasementioning
confidence: 99%